Importance of the central axes of the Brazilian Health Reform for the principles of the Unified Health System: reflections for the resistance to the neoliberal advance - Laurindo, Cosme Rezende (2022)
The objective of this study is to analyze the importance of building the principles of the Unified Health System (UHS) from the categories “Model of Social Determination” and “Process of Work in Health”, central axes of the Brazilian Health Reform (BHR). It is a reflective analysis based on a non-systematized literature review. Theoretical and conceptual frameworks were established in the light of the field of public health. The analysis was carried out in proximity to dialectical historical materialism, taking into account the assumptions of dynamicity and historicity. The development of the study is organized in: socio-historical analysis of health policies in Brazil until the mid-1980s; contextualization and conceptualization of the BHR Movement; and the analysis of the Model of Social Determination and the Process of Work in Health as central categories for the construction of SUS principles. Despite being brief, this study promoted reflection on the importance of building UHS principles from the central axes of BHR and Collective Health. It was possible to recover the historical paths taken to arrive at the philosophical, epistemological and ideological bases of the UHS, essential for the construction of a system based on the needs of the population and on non-alienation in the face of market rules. Thus, it becomes a powerful instrument for discussion in the interdisciplinary field of health and resistance to neoliberal advances, envisioning the scope of the UHS effectiveness.